2010
DOI: 10.1080/03033910.2010.10446322
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of School Bullying, Psychological Well-being and Stress in Northern Ireland

Abstract: Little is known about the levels and psychological consequences of bully/victim behaviours in schools in Northern Ireland. The aim of the present study was to examine the prevalence of self-reported experiences of school bullying, and the relationship between such experiences, stress and general psychological health. A random sample of 824 twelve-to seventeenyear-olds living throughout Northern Ireland completed a questionnaire booklet as part of the 2004 "Young Life and Times" survey. Respondents completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Devine and Lloyd () found similar results in their Northern Irish sample of primary students (10–11 years) who had significantly poorer psychological well‐being than their peers when exposed to cyberbullying. Mc Guckin () also found that there were significant associations between victimization and poorer psychological well‐being for a sample of 16‐year‐olds in Northern Ireland.…”
Section: Resultsmentioning
confidence: 95%
“…Devine and Lloyd () found similar results in their Northern Irish sample of primary students (10–11 years) who had significantly poorer psychological well‐being than their peers when exposed to cyberbullying. Mc Guckin () also found that there were significant associations between victimization and poorer psychological well‐being for a sample of 16‐year‐olds in Northern Ireland.…”
Section: Resultsmentioning
confidence: 95%
“…McGuckin et al . (2010) caution that if you do not understand cyber safety you cannot teach it. In light of the current findings, CAMHS staff may benefit from training in CB and IS to ensure they have the necessary competencies to support clients online behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Fernández 2009) or related to specific categories of SEN/disability (e.g. Symes 2010a, 2010b;Unnever and Cornell 2003), this has occurred on a sporadic and less than systematic manner, like much research in the area of bully/victim problems (Mc Guckin, Lewis, and Cummins 2010b). Despite this, a common finding in international research is that there are higher incidence rates among children with SEN than among those without (e.g.…”
Section: Disablist Bullyingmentioning
confidence: 96%